The Relationship Between the Change Management and the Operational Excellence in Electrical and Electronics Manufacturing Companies - Ahmad, Hartini; Alekam, Jamal Mohamed Ismail; Shaharruddin, Sarah; Marchalina, Leonis; Fok-Yew, oon (International Journal of Supply Chain Management, 2018)
Purpose – The purpose this paper is to examine the relationship between the change management and the operational excellence in the manufacturing companies (i.e. electrical and electronics). Design/ methodology/ approach –This study utilizes causal study using survey methods to ascertain the relationship between the management of change and operational excellence. The samples of the population were selected for the Electrical and Electronics sectors using the systematic random sampling method. Findings – The analysis found significant positive relationships between organic structure, operations strategy, transformational leadership style and human resource practices on operational excellence. The operations strategy influenced the most on the operational excellence. Research implications – The results of this study could promote a better understanding of the operational excellence in the electrical and electronics industry and its implications for activities concerning operation management and change management. Therefore, the recommendation to management is to establish policy, systems, and processes by integrating both hard elements (structure and strategy) and soft elements (leadership and human resource) in a strategic planning of the companies. This study is hoped to contribute to a body of knowledge, in terms of the insight into an achievement of the operational excellence. As it focuses on a proper integration of organic structure, operations strategy, transformational leadership style and human resource practices.